VD_FINDINFO Jug / 2011 / 214 vom 22. Juni 2011 - VD Tribunal cantonal (2011)
DISPOSITIONS PÉNALES DE LA LCR, SURSIS À L'EXÉCUTION DE LA PEINE, RÉVOCATION DU SURSIS | 42 al. 1 CP, 42 al. 4 CP, 46 al. 2 CP, 90 ch. 2 LCR